Adaptation of the Token Test in Standard Indonesian - Jap, Bernard A. J.; Arumsari, Chysanti (Makara Human Behavior Studies in Asia, 2017)
Aphasia is a language disorder caused by focal brain injury. The Token Test is a tool to detect aphasic symptoms and measure aphasic severity in individuals who suffer brain damage causing language impairment. While Indonesia has a diagnostic test battery for aphasia (TADIR), it has yet to be able to quantify aphasic severity. In this study, we tested 49 individuals: 26 healthy adults, 7 non-aphasic post-stroke individuals, and 16 aphasic individuals. A series of tests were administered: the TADIR, Token Test, and the Verb and Sentence Test. The Token Test was sensitive enough to distinguish between the three groups and was also correlated with all other language tests including the TADIR.